Communication, Consent, and Clinical Hierarchies: Reflections from a Medical Elective in the Philippines. - Hirst, Lucy (Advanced Journal of Professional Practice, 2025)
This article reflects on an elective placement in the Philippines, undertaken by a fourth-year medical student. It discusses disparities in healthcare systems, approaches to informed consent, communication practices, and the impact of clinical hierarchy on learning. The article aims to give insight into the ethical and cultural challenges in global practice and show the benefits of international electives for medical students, particularly the opportunities for improving clinical knowledge, ethical awareness, and adaptability.